Gene targeting - Vega, Manuel A. (CRC Press, 1995)
This book examines the revolutionary new technology of gene targeting, from its history to its potential application for the genetic treatment of human diseases. It begins with an introduction to the field and a description of the whole gene targeting spectrum. It continues with discussions in the following areas: The molecular mechanisms of the homologous recombination reactions lying behind gene targeting technology The application of gene targeting approaches to the problems of tripanosomatide biology and etiopathology The concept of gene targeting on plant genes and its impact on plant genetic engineering The current knowledge on mammalian development and physiology and its relationship to gene targeting technology The application of gene targeting technology, as well as other genetic techniques, to the production of animal models for human diseases The enzymatic complexes and components participating in natural bacterial DNA recombination and their potential application to gene targeting technology The potential application of gene targeting for the genetic treatment of human diseases